Underground Movements : Modern Culture on the New York City Subway - Stalter-Pace, Sunny, 1977- (Book collections on Project MUSE., 2013)
For more than a century, the New York City subway system has been a vital part of the city's identity, even as judgments of its value have varied. It has been celebrated as the technological embodiment of the American melting pot and reviled as a blighted urban netherworld. This book explores the many meanings of the subway by looking back at the era when it first ascended to cultural prominence, from its opening in 1904 through the mid-1960s. The author analyzes a broad range of texts written during this period - news articles, modernist poetry, ethnic plays, migration narratives, as well as canonical works by authors such as Hart Crane, William Carlos Williams, and Ralph Ellison - to illustrate the subway's central importance as a site of abstract connection, both between different parts of the city and between city dwellers who ride the train together.